Gender Perspectives on Political Awareness and Participation in the Digital Era Ugyal Tshering Lama Yolmo - Digital Era Ugyal Tshering Lama Yolmo
This study is a crucial element of a broader initiative to evaluate political participation and awareness among university students. It was a mixed-method study comprising a survey to examine the political awareness and participation levels and a semi-structured interview to examine gender differences. The article outlines the gender differences in political awareness and political participation and the reasons for them, according to respondents. The results showcase that there was a significant gender difference in political awareness (t = 1.976, p < .05) and political participation (t = 4.575, p < .005). Analysis of the interviews revealed barriers to women$1 (Bs political awareness and participation. The study addresses the gender difference and barriers and recommends strategies to overcome those barriers.s